Occurrence and Origin of Gypsum Deposits at Jamsar and Pallu in Northwest Rajasthan - Sundaram, R M; Rakshit, P (Annals of Arid Zone, 2016)
Surface and near-surface Quaternary gypsum deposits of lacustrine and pedogenetic origins are abundant in northwest Rajasthan. The lacustrine forms are horizontally bedded gypsum deposits and pedogenetic crusts are massive, nodular and powdery pans. The lacustrine gypsum deposits are the locales of palaeolake basins and are in association with a serir surface. The pedogenetic gypsum pans occur in pockets along the palaeochannels, especially in the dune country. The influence of climatic variation and the control of tectonism are discussed on the basis of observations at Jamsar and Pallu in northwest Rajasthan.